Hyperglycemia duration impact on anatomical damage level of osteoarthritic articular cartilage in rat models with diabetes mellitus type 1 - Ibrahim Njoto (Russian Open Medical Journal)
Background — Diabetes mellitus caused alteration of chondrocytes morphology of superficial layer on osteoarthritic articular (OA) cartilage in an articular cartilage rat model. These results need to be analyzed in relation to hyperglycemia duration. Objective — This study evaluates the influence of hyperglycemia on microscopic anatomical damage progression in OA cartilage. Material and Methods — Thirty-five adult male rats were divided into seven groups: control group, three OA groups, and three OA groups with type 1 diabetes mellitus (DMT-1). For OA groups, the first, second, and third group was sacrificed on the third, fourth, and sixth week respectively after two months maintenance. OA with DMT-1 groups were performed anterior cruciate ligament transaction (ACLT) and were injected streptozotocin intraperitoneally to promote DMT-1 for one-month maintenance. DMT-1.1, DMT-1.2, and DMT-1.3 group was sacrificed on the third, fourth, and sixth week respectively after two months maintenance. The right knee cartilage was taken and processed for histopathology with hematoxylin and eosin staining, then analyzed using a Pritzker scale. Results — In OA group with DMT-1, hyperglycemia duration (6th>4th>3th weeks exposure) increased the level of damage in the OA cartilage compared with the OA group. Pritzker scale observe on deeper abrasiveness of the superficial articular layer, cartilage fissure reaching the middle layer, a more severe decrease in the chondrocytes columnar pattern, changing of matrix integrity, and many sclerotic conditions were provoked by increasing the hyperglycemia duration. Conclusion — Hyperglycemia duration influenced the damage level in the articular cartilage, increasing the progression of OA disease in animal models.